Individual Feed Intake of Transition Cows and Their Daily Activity Measures of Temperature, Eating, Rumination, Resting, and Activity Times - J. S. Stevenson; C. S. Takiya; B. J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2019)
Fifteen transition dairy cows bearing CowSensor®ear tags were monitored during 14 days before and after calving to assess temperature and behavior outcomes recorded by the sensors, in addition to actual individual dry matter and as-fed feed intake. The sensors—compared with reported visual observation studies—underestimated eating and resting times, but rumination time was estimated reasonably accurately. Expected changes in rumination (decreased acutely before calving and increased linearly to day 14) and general activity (increased acutely just before calving) were observed. More studies are warranted to determine how to use these activity monitors in detecting health disorders of cows that affect milk yield.
Keywords: behavior monitoring; sensor; validation